Access Control Model Scheme based on Policy Grading in Natural Language Processing Blockchain Environment - Huang, Jie; Wu, Dehua (Mobile Information Systems, 2022)
In order to solve many problems such as secure storage of access policies and distrust of third parties in complex and dynamic big data environment, a hierarchical access control model under block chain environment (BP-ABAC) is proposed. Access control policies are stored in blockchain in the form of smart contracts, and access control policies are classified in contract design. Users can obtain the access permission of the corresponding policy set according to the rating evaluation. Access to a resource is obtained when the request attribute matches the policy in the policy set. The simulation results show that the model can grant corresponding access control permissions according to different users’ access requests, improve the time efficiency and accuracy of the access control process, and improve the security and privacy of the storage of access policies and the interaction of data sharing.